Preparation of herbal Shrikhand using Catharanthus roseus powder - Singh, Shubhendra; Kashyap, Saloni; V.P, Aparnna; Chauhan, Anil Kumar (Indian Journal of Dairy Science, 2022)
The purpose of this study was to develop herbal Shrikhand by incorporating Catharanthus roseus powder and adding stevia as a sweetener. The analysis was carried out by adding Catharanthus roseus leaf powder to the product at the rate of 0%(T0), 2%(T1), 4%(T2), 6%(T3) and Stevia added at 4% to each. Prepared herbal Shrikhand was further analysed and the sensory evaluation revealed that T1 combination was best accepted as compared other samples. The T1 combination was selected as the optimized product for further microbial analysis. Microbial activity of the product stored at 4Â°c was evaluated at intervals of 7 days. The cost of preparation was also estimated for the optimized product. Herbal Shrikhand was found to be better in nutritional content for diabetics and the product was acceptable up to 28 days while control sample was acceptable up to 7 days only.